Pengembangan Moderasi Beragama Bagi Pengajar TPA Dan Takmir Masjid Di Desa Lemahbang Kecamatan Jumapolo Kabupaten Karanganyar - Mukhlis Fathurrohman; Viki Bayu Mahendra; Difaudin Alasykari; Muhammad Raihan Al-Firdaus (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of this service is to increase religious moderation for teachers at the Al-Qur'an Education Park and Mosque Takmir in Lemahbang village, Jumapolo sub-district, Karanganyar district so that in carrying out their social activities they can provide coolness and provide a message of peace, especially for the children of the Al-Qur'an Education Park and the community. common for the Takmir of the Mosque. This service was carried out with consideration because Lemahbang village consists of many mass organizations, including Muhammadiyah, Nahdlatul Ulama, Al-Qur'an Tafsir Council, Indonesian Da'wah Council Institute and others. This service activity was carried out in Lemahbang village, Jumapolo subdistrict, Karanganyar district in February 2023. Lemahbang subdistrict consists of 20 RTs and 8 RWs and there are 8 villages in it. This activity involved Al-Qur'an Education Park teachers and mosque Takmirs throughout Lemahbang village which was carried out through three phases, namely preparation, implementation and evaluation. This religious moderation service activity is based on 4 things, namely tolerance, accommodating local culture, national commitment and non-violence. The results of this service show that the four things that underlie religious moderation are implemented well by the teachers at the Al-Qur'an Education Park and Takmir mosque in Lemahbang village. This happens because of their commitment to maintaining the calm of Lemahbang village where they live.